Forecast of the bidding curve of generation players in the Iberian electricity market - Rúben A. Soares (2015)
This paper reports the research that was developedto predict biding curves submitted by generation players to theMarket Operator of the Iberian Electricity Market. In thisscope, we used a data set based on publicly availableinformation from the website of the Market Operator to developa two-step ANN prediction model. The first step involves theprediction of the amount of energy bidden at zero price and thesecond ANN predicts the parameters of the equation of the linethat better approximates the remaining bid curve. The testswere done using information of a large generation player butthis approach can be replicated to other players so that theindividual predicted curves can be composed in order to obtainthe aggregated selling curve for each hour of the next day.